Polyethylene-based nanocomposites containing organoclay: A new approach to enhance gas barrier via multilayer coextrusion and interdiffusion. (20th March 2015) - Decker, Jeremy J.; Meyers, Kevin P.; Paul, Donald R.; Schiraldi, David A.; Hiltner, Anne; Nazarenko, Sergei
Abstract: Layer multiplying coextrusion was employed to produce films consisting of alternating layers of unfilled and particulate filled polymers, i.e., low density polyethylene (LDPE) and maleic anhydride grafted linear low density polyethylene (LLDPE-g-MA)/organoclay nanocomposites. Layer multiplying coextrusion was employed to produce gas barrier films consisting of alternating layers of unfilled and particulate filled polymers, i.e., low density polyethylene (LDPE) and maleic anhydride grafted linear low density polyethylene (LLDPE-g-MA)/organoclay nanocomposite. To further enhance gas barrier performance, the clay concentration within the nanocomposite layers was increased several fold through annealing of the multilayer film in the melt state. Residing in the melt state activated the interdiffusion between the polymers and due to a significant difference in the molecular mobility between the LDPE and LLDPE-g-MA chains led to a moving boundary effect which contracted the (LLDPE-g-MA)-rich nanocomposite layers and expanded the LDPE-rich layers. Analysis of the clay morphology within the nanocomposite layers demonstrated an increase in the clay particle lengths and aspect ratios, which was attributed to the growth of "skewed" aggregates during layer contraction and particle concentration. The melt induced clay concentration and increased clay particle dimensions caused a significant decrease in oxygen permeability of the nanocomposite layers and reduced the overall permeability of the multilayered films. Morphology and transport behavior of the multilayered films were compared to a series of LLDPE-g-MA/clay bulk nanocomposites with varying clay content prepared by melt compounding in a twin screw extruder. Nielsen and Cussler models were used to describe the gas barrier data of the nanocomposite films. Although both models can be fit well to the experimental data, the Cussler model showed a better agreement with the morphological observations. Graphical abstract: